Mauro, Chiara Maria (2019), Archaic and Classical Harbours of the GreekWorld, Archaeopress Archaeology, Oxford, 115 pp., ISBN: 978-1-78969-128-3. (Cuadernos de Arqueología de la Universidad de Navarra, 2020)
‧‧